MSME Data Collection Team Formation Program in Jamali Village, Cianjur Regency: Collaboration of LLDIKTI III Regional Universities - Rooshwan. B U; Mufid Suryani; Sumarsid Sumarsid; Arifin Arifin; Jayadi Jayadi; R. Iriana W S; Harry Wiyanto; Dewi K; Nani Sunarni; Siti Syamsiah; Theodorus Theodorus; Turah Turah; Dessy A (Jurnal Pengabdian Pancasila (JPP), 2025)
Jamali Village in Cianjur Regency has great potential in the Micro, Small and Medium Enterprises (MSMEs) sector, but does not yet have integrated and accurate data as a basis for policy making. This community service activity aims to form a MSME data collection team involving the collaboration of several universities under the coordination of LLDIKTI Region III, namely Gunadarma University, Labora Management College, ISWI Academy of Fine Arts & Design, and Perbanas Institute. Activities included basic data collection training, preparation of survey instruments, implementation of field data collection, and digitization of MSME data. As a result, a village data collection team consisting of residents and students was formed, and an initial database of Jamali Village MSMEs was compiled. This collaboration shows the real synergy between the world of higher education and the community in supporting data-based village economic development.